Critical factors for private-public partnership (PPP) in urban and environmental infrastructure in Jilin Province, China. - Zhou, Mengmeng. (2017)
Abstract: With rapid economic growth, industrialization, and urbanization, industrial and household waste gradually degrades the living environment, which leads to the need to increase the quality and quantity of urban and environmental infrastructure. Public Private Partnership (PPP) is perhaps one of the most innovative developments in helping to reduce the fiscal burden of governments, and to speed up building or updating urban and environmental protection infrastructure, and then to meet the need for environment protection. It provides a sound basis for a ``win-win'' and synergistic teamwork. PPP in urban infrastructure has become more popular since it was introduced into China in the mid-1990s. However, less developed cities, such as Baicheng in Jilin Province, are still lacking of PPP experience. This thesis presents a review of critical factors for partnering projects in general and specially for Jilin Province perspective. The results indicate that certain requirements must be met for PPPs to succeed. In particular, thoughtful project analysis, clear definition of responsibilities and obligations, willingness to share risks among project participants, commitment to a win-win attitude, and regular monitoring of partnering process are the significant factors. A full-fledged legal system and dedicated PPP departments or organizations are the foundations for promoting PPP development.; Thesis (M.A.)--Tufts University, 2015.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Weiping Wu.; Committee: Lorlene Hoyt.; Keyword: Urban planning.